1992
DOI: 10.2535/ofaj1936.68.6_365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Starvation on the Water-Clear Cell in the Golden Hamster Parathyroid Gland

Abstract: Summary:Changes of the water-clear cells of the parathyroid glands in adult and senile golden hamsters 2 and 5 days after starvation were investigated. Albright et al. (1934) first reported the waterclear cell hyperplasia of the parathyroid glands in patients with primary hyperparathyroidism, and several authors have described the ultrastructure of the water-clear cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Our study have shown that lipid droplets were very numerous in water-clear cells as well as in chief cells in the golden hamsters after starvation (Emura et al, 1992b).…”
mentioning
confidence: 50%
“…Our study have shown that lipid droplets were very numerous in water-clear cells as well as in chief cells in the golden hamsters after starvation (Emura et al, 1992b).…”
mentioning
confidence: 50%
“…Human beings and hamsters have parathyroid glands that develop from the third and fourth branchial pouches [ 17 ]. Hamsters have only two parathyroid glands, but humans have four glands in close proximity to the thyroid gland [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…Human beings and hamsters have parathyroid glands that develop from the third and fourth branchial pouches [ 17 ]. Hamsters have only two parathyroid glands, but humans have four glands in close proximity to the thyroid gland [ 17 ]. Under a light microscope, the parenchyma of the parathyroid gland is made of basal cells and chief cells, which are suprabasal and oxyphil cells [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations